KEWENANGAN INDEPENDENSI HAKIM DALAM PENERAPAN PIDANA MINIMAL KHUSUS (STUDI KASUS: PUTUSAN NOMOR 144/PID.SUS/2019/PN KDS) - Tamara Arruum Shafira; R. Rahaditya (Jurnal Hukum Adigama, 2021)
Every single year, cases of sexual crimes have increased. The number of victims is not only from adults but has also spread to adolescents, children and toddlers. Children are a group that is very vulnerable to sexual crimes because children are always positioned as weak or powerless and have a high dependence on the adults around them. In almost every case disclosed, the perpetrator is the closest person to the victim and not a few perpetrators are people who dominate the victim, such as parents and teachers. We recognize sexual crimes as a form of sexual violence against children involving the role of children in all forms of sexual activity that occur before the child reaches a certain age limit established by the laws of the country concerned where an adult or other child who is older or someone who is considered to have better knowledge of the child using it for sexual pleasure or sexual activity. In carrying out this act, usually many of the perpetrators used force, threats, bribes, tricks and even pressure.